Maresin 1 mitigates LPS‐induced acute lung injury in mice - Gong, Jie; Wu, Zhou‐yang; Qi, Hong; Chen, Lin; Li, Hong‐bin; Li, Bo; Yao, Cheng‐ye; Wang, Ya‐xin; Wu, Jing; Yuan, Shi‐ying; Yao, Shang‐long; Shang, You (British journal of pharmacology, 2014)
Background and Purpose Acute lung injury (ALI) is a severe illness with a high rate of mortality. Maresin 1 (MaR1) was recently reported to regulate inflammatory responses. We used a LPS‐induced ALI model to determine whether MaR1 can mitigate lung injury. Experimental Approach Male BALB/c mice were injected, intratracheally, with either LPS (3 mg·kg−1) or normal saline (1.5 mL·kg−1). After this, normal saline, a low dose of MaR1 (0.1 ng per mouse) or a high dose of MaR1 (1 ng per mouse) was given i.v. Lung injury was evaluated by detecting arterial blood gas, pathohistological examination, pulmonary oedema, inflammatory cell infiltration, inflammatory cytokines in the bronchoalveolar lavage fluid and neutrophil–platelet interactions. Key Results The high dose of MaR1 significantly inhibited LPS‐induced ALI by restoring oxygenation, attenuating pulmonary oedema and mitigating pathohistological changes. A combination of elisa and immunohistochemistry showed that high‐dose MaR1 attenuated LPS‐induced increases in pro‐inflammatory cytokines (TNF‐α, IL‐1β and IL‐6), chemokines [keratinocyte chemokine, monocyte chemoattractant protein‐5, macrophage inflammatory protein (MIP)‐1α and MIP‐1γ], pulmonary myeloperoxidase activity and neutrophil infiltration in the lung tissues. Consistent with these observations, flow cytometry and Western blotting indicated that MaR1 down‐regulated LPS‐induced neutrophil adhesions and suppressed the expression of intercellular adhesion molecule (ICAM)‐1, P‐selection and CD24. Conclusions and Implications High‐dose MaR1 mitigated LPS‐induced lung injury in mice by inhibiting neutrophil adhesions and decreasing the levels of pro‐inflammatory cytokines.